SIMILITUDE METHOD – ANOTHER METHOD OF OBTAINING EINSTEIN AND FRIEDMAN METRICS IN COSMOLOGY - Abdildin, M.M.; Beissen, N.A.; Taukenova, A.S. (Recent Contributions to Physics, 2018)
This work shown that the similitude method provides us by simple way to obtain cosmological solutions of Einstein and Friedmann.